2019
DOI: 10.1515/iss-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

No need for surgery? Patterns and outcomes of blunt abdominal trauma

Abstract: IntroductionThe management of a patient suffering from blunt abdominal trauma (BAT) remains a challenge for the emergency physician. Within the last few years, the standard therapy for hemodynamically stable patients with BAT has transitioned to a non-operative approach. The purpose of this study is to evaluate the outcome of patients with BAT and to determine the reasons for failure of non-operative management (NOM).Materials and methodsAnalysis of 176 consecutive patients treated for BAT was conducted in a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…In our study, the initial nonoperative treatment rate was 58.44%, with an approximate success rate of 90%, a finding which is higher as compared with other reported series (32). We accept that the complication rate of 16.88% and the surgical intervention rate of 37% in our study was higher but comparable with the other reported studies where the reported rate was 10 to 27% (33,34). The learning curve of the treating trauma team as well as the supporting paramedical staff was one of the predominant contributory factors.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, the initial nonoperative treatment rate was 58.44%, with an approximate success rate of 90%, a finding which is higher as compared with other reported series (32). We accept that the complication rate of 16.88% and the surgical intervention rate of 37% in our study was higher but comparable with the other reported studies where the reported rate was 10 to 27% (33,34). The learning curve of the treating trauma team as well as the supporting paramedical staff was one of the predominant contributory factors.…”
Section: Discussionsupporting
confidence: 75%
“…4,5,8,10,11 Currently, primary surgery is only necessary to treat severe hepatic injury cases associated with hemodynamic instability. 10,11,23,24 Our patient presented with a grade V liver injury. Although the patient's hemodynamics were initially unstable, the patient responded to fluid resuscitation, enabling hemostatic treatment by interventional radiology.…”
Section: Discussionmentioning
confidence: 81%
“…The fatality depends on the delay in emergency laparotomy and advanced age. 17,18 So, the success of operating management in NOM patients going for surgery and primary operating management depends on the perfect timing of surgery. Young people tolerate delay better then elderly, single organ better than multiple and small surface of bleed than larger.…”
Section: Discussionmentioning
confidence: 99%
“…Young people tolerate delay better then elderly, single organ better than multiple and small surface of bleed than larger. 16,17,18 . There were 20 of 72(27.7%) patient, who required operative management, without thinking of failure but to save life.…”
Section: Discussionmentioning
confidence: 99%